Contemporary Issues of Islamic Family Law: The Waithood Phenomenon and the Impact of the Sex Recession in Indonesia in Review of Sadd al-dzari'ah - Muhammad Hafis; Nia Elmiati; Juliani Syafitri (Legitima: Jurnal Hukum Keluarga Islam)
Purpose – This research aims to examine the phenomena of waithood (delaying marriage) and sex recession as contemporary issues in Islamic family law in Indonesia. Both phenomena demonstrate complex social dynamics, which not only affect family structures but also have far-reaching impacts on social, cultural, religious and educational dimensions. Using the sadd al-dzari'ah approach, this research seeks to identify the root of the problem and offer solutions that are in accordance with the principles of Islamic family law.